REFORMASI KEBIJAKAN PERDAGANGAN DAN INDUSTRI - Santosa, Agus Budi (Fokus Ekonomi, 2007)
Two most important events in developing countries that occurred in the beginning 1980s, are debt crisis and the stagnant of inward looking policy. It revealed ideas on reforming the trading industry policy. The reformation process was supported by the World Bank with its Structural Adjustment Loans (SAL’s). In that program, reformation is directed to the permission problems and the tariff disturbances with the target of the efficiency of the actor of economic sector both private and government. In this paper, it is explained reformation of alternative policy, that is: strategic trading policy, the policy to promote industry with economical scale and the policy of knowledge promotion and growth. Keyword: Structural Adjustment Loans, Inward Looking, Tariff.